DEVELOPMENT OF COD (CHEMICAL OXYGEN DEMAND) ANALYSIS METHOD IN WASTE WATER USING UV-VIS SPECTROPHOTOMETER - Uswatun Hasanah; Ade Heri Mulyati; Sutanto .; Diana Widiastuti; Siti Warnasih; Yulian Syahputri; Tri Panji (Universitas Pakuan, 2020)
The COD (Chemical Oxygen Demand) analysis method based on the Indonesian National Standard (SNI) is a revision of SNI 06-6989.2-2004, Water and wastewater - Part 2: Method of testing for chemical oxygen demand (COD) with closed reflux spectrophotometrically. This SNI uses references from international standard methods, namely Standard Methods for the Examination of Water and Wastewater, 21st Edition, editor of LS Clesceri, AE Greenberg, AD Eaton, APHA, AWWA and WEF, Washington DC, 2005, Methods 5220 D (Closed Reflux, Colorimetric Methods). The purpose of this study was to validate the total method for testing chemical oxygen demand (COD) in water and wastewater with the reduction of Cr2O7 2- spectrophotometrically in the range of COD values of 100 mg / L to 900 mg / L measurements were made at a wavelength of 600 nm. and COD values less than or equal to 90 mg / L measurements were made at a wavelength of 420 nm. The results showed that the method SNI 06-6898.2- 2009 has good validation results including the r results obtained from the calibration curve equation of 0.998, a precision of 1.82%, an accuracy of 98.25% and LOD and LOQ of 12.27 mg / L and 25, 61 mg / L.